Three-dimensional reconstruction of prostate cancer architecture with serial immunohistochemical sections: hallmarks of tumour growth, tumour compartmentalisation, and implications for grading and heterogeneity - Tolkach, Iurii; Thomann, Stefan; Kristiansen, Glen (Histopathology, 2018)
Aims Conventional morphology of prostate cancer considers only the two-dimensional (2D) architecture of the tumour. Our aim was to examine the feasibility of three-dimensional (3D) reconstruction of tumour morphology based on multiple consecutive histological sections and to decipher relevant features of prostate cancer architecture. Methods and results Seventy-five consecutive histological sections (5 μm) of a typical prostate adenocarcinoma (Gleason score of 3 + 4 = 7) were immunostained (pan-cytokeratin) and scanned for further 3D reconstructions with fiji/imagej software. The main findings related to the prostate cancer architecture in this case were: (i) continuity of all glands, with the tumour being an integrated system, even in Gleason pattern 4 with poorly formed glands—no short-range migration of cells by Gleason pattern 4 (poorly formed glands); (ii) no repeated interconnections between the glands, with a tumour building a tree-like branched structure with very ‘plastic’ branches (maximal depth of investigation 375 μm); (iii) very stark compartmentalisation of the tumour related to extensive branching, the coexistence of independent terminal units of such branches in one 2D slice explaining intratumoral heterogeneity; (iv) evidence of a craniocaudal growth direction in interglandular regions of the prostate and for a lateromedial growth direction in subcapsular posterolateral regions; and (v) a 3D architecture-based description of Gleason pattern 4 with poorly formed glands, and its continuum with Gleason pattern 3. Conclusions Consecutive histological sections provide high-quality material for 3D reconstructions of the tumour architecture, with excellent resolution. The reconstruction of multiple regions in this typical case of a Gleason score 3 + 4 = 7 tumour provides insights into relevant aspects of tumour growth, the continuity of Gleason patterns 3 and 4, and tumour heterogeneity.
Gesehen am 12.08.2019